Potassium Release and Exchange Characteristics of the Selected Wetland Rice Soils of Kerala - Louis Joseph (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1994)
Being in the humid tropics, the pedogenic environment prevailing in kerala keeps the soil inherently deficient in the status of potassium. The exchange and release patterns of potassium was studied using typical wet land soils viz. Black cotton soils of Chittoor, sandy Onattukara of Kayamkulam and laterite alluvium of Pattambi. This investigation gives a deeper insight into the potassium supplying capacity of these soil types of Kerala. From the basic chemical analysis of the soils, it was revealed that the black cotton soils are high in clay content (%) and potassium fixation and supplying capacity are also high. In sandy Onattukara the clay content is very low (15 %) and hence the fixation and potassium content were found to be low while in lateritic alluvium eventhough the clay content is high (25%) the potassium content and fixation is low due to the kaolinitic nature of the clays. A study on the cumulative potassium removal by continuous flooding with water and leaching with neutral normal ammonium acetate revealed that the total potassium removed by seven successive leachings to be 12.8 mg, 2.28 mg and 11.4 mg k in black cotton, sandy Onattukara and lateritic alluvium soil respectively. But the potential capacity of supplying k in these soils as estimated by chemical analysis was found to be 85.5, 31.0 and 29.5 mg k/kg soil indicating a situation where the analytical procedures give much higher estimate than that is actually available under field conditions. From another experiment to find the total potassium supplying capacity of these soils by crop exhaustion studies, it was found that the total potassium supplied by these soils amounted to 306, 15.44 and 14.27 mg k/kg soil. However the black cotton soil alone remained undepleted even after seven successive cropping with rice. The high amount of potassium supplied by Black cotton soil was due to the high content of fixed k, while in sandy Onattukara and lateritic alluvium the low content of fixed potassium, low clay content and low CEC explains the low availability of potassium. When we compare the amounts of potassium obtained by crop exhaustion with the amount of k removed by leaching it may be noted that leaching studies provided an under estimated value. This might be due to the reversible equilibrium possible between soils k and that extracted by ammonium acetate during leaching, where as under exhaustive cropping the plant root continuously removed k from the system there by creating a concentration gradient between soil K and solution rendering no chance for such an equilibrium. The response studies carried out in the above depleted two soils – Sandy Onattukara and Lateritic alluvium with different levels of applied K (0 k, ¼ k, ½ k, 1 k, 1 ½ k, and 2 k. Where K represents cumulative K removal by crop exhaustion) showed that biometric characters, yield attributes and nutrient content showed an increasing trend with increase in the levels of applied K. The response was maximum at 2 K levels. The response applied K showed a linear pattern.